2015
DOI: 10.1002/14651858.cd002229.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy for preventing cardiovascular disease in post-menopausal women

Abstract: Analysis 2.11. Comparison 2 Combination HT vs placebo in primary prevention, Outcome 11 Non-fatal MI: time on treatment..... Analysis 3.1. Comparison 3 Estrogen vs placebo in secondary prevention, Outcome 1 Death (all causes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
289
0
32

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(365 citation statements)
references
References 205 publications
7
289
0
32
Order By: Relevance
“…The effects of hormone therapy on coronary heart disease (CHD) may vary depending on when hormone therapy is initiated in relation to a woman's age and/or time since menopause onset, with data suggesting reduced risk of CHD 11 in women who initiate hormone therapy aged younger than 60 years and/or within 10 years of menopause onset. However, for women who initiate hormone therapy more than 10 years or clearly by 20 years from menopause onset, risk of CHD appears increased 12 .…”
Section: Major Findings From the 2017 Hormone Therapy Position Statemmentioning
confidence: 99%
“…The effects of hormone therapy on coronary heart disease (CHD) may vary depending on when hormone therapy is initiated in relation to a woman's age and/or time since menopause onset, with data suggesting reduced risk of CHD 11 in women who initiate hormone therapy aged younger than 60 years and/or within 10 years of menopause onset. However, for women who initiate hormone therapy more than 10 years or clearly by 20 years from menopause onset, risk of CHD appears increased 12 .…”
Section: Major Findings From the 2017 Hormone Therapy Position Statemmentioning
confidence: 99%
“…4 It is also associated with less progression of subclinical atherosclerosis compared to placebo. 5 Even sub-analysis of the WHI study has shown that there is no increased risk of cardiovascular disease in women starting HRT within 10 years of the menopause.…”
Section: Benefits Of Hrtmentioning
confidence: 99%
“…В них тера-пия назначалась в ранней постменопаузе, были ис-пользованы различные эстрогены/прогестины и пу-ти их введения, а также применялись более низкие дозы гормонов по сравнению с WHI [38][39][40]. Резуль-таты нового кохрейновского обзора данных выявили снижение риска ИБС (относительный риск (ОР) 0,52; 95% ДИ 0,29-0,96) и общей смертности (ОР 0,70;95% ДИ 0,52-0,95) у женщин, начавших МГТ в течение первых 10 лет постменопаузы, фактически единственным серьезным неблагоприятным эффек-том явилось повышение риска венозной тромбоэм-болии [41]. Связанный с использованием MГT риск серьезных событий венозной тромбоэмболии явля-ется крайне низким у здоровых более молодых жен-щин, поэтому важно выявление предрасположенных к таким нарушениям женщин перед назначением МГТ и использование препаратов и режимов МГТ, оказывающих минимальное воздействие на меха-низмы тромбогенеза [42].…”
Section: пост-Whiэра: «окно терапевтических возможностей» мгтunclassified